1986
DOI: 10.1038/319234a0
|View full text |Cite
|
Sign up to set email alerts
|

Primate η-globin DNA sequences and man's place among the great apes

Abstract: Molecular studies indicate that chimpanzee and gorilla are the closest relatives of man (refs 1-7 and refs therein). The small molecular distances found point to late ancestral separations, with the most recent being between chimpanzee and man, as judged by DNA hybridization. Kluge and Schwartz contest these conclusions: morphological characters group a chimpanzee-gorilla clade with the Asian ape orang-utan in Kluge's cladistic study and with an orang-utan-human clade in Schwartz's study. Clearly, extensive se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(96 citation statements)
references
References 39 publications
10
83
3
Order By: Relevance
“…Within mammals there is considerable evidence for evolutionary rate heterogeneity, with different mammal groups evolving at different rates (28)(29)(30)(31)(32)(33)(34)(35)(36)(37), although this finding has been questioned (38). While some studies run contrary to this finding (39,40), there is also considerable evidence for rate heterogeneity within primates, particularly that hominoids are evolving slower than cercopithecoids (the ''hominoid slowdown'') (15,32,34,(41)(42)(43)(44)(45)(46)(47). These findings conflict with the proposition of a global molecular clock for mammals (23).…”
mentioning
confidence: 79%
“…Within mammals there is considerable evidence for evolutionary rate heterogeneity, with different mammal groups evolving at different rates (28)(29)(30)(31)(32)(33)(34)(35)(36)(37), although this finding has been questioned (38). While some studies run contrary to this finding (39,40), there is also considerable evidence for rate heterogeneity within primates, particularly that hominoids are evolving slower than cercopithecoids (the ''hominoid slowdown'') (15,32,34,(41)(42)(43)(44)(45)(46)(47). These findings conflict with the proposition of a global molecular clock for mammals (23).…”
mentioning
confidence: 79%
“…This problem can be circumvented partly by statistical correction (Miyata et al 1980). Moreover, it could be shown that the evolutionary rate has significantly slowed down during primate evolution (Chang and Slightom 1984;Goodman et al 1984;Li et al 1985;Koop et al 1986;Sakoyama et al 1987), whereas rodents appear to be one of the most rapidly evolving mammalian orders Wu and Li 1985;Harlow et al 1988). Because of these intra-as well as interorder differences, no universal silent molecular clock for mammals is applicable [for a detailed evaluation of the molecular clock in mammals see Li et al (1987)], and we therefore decided to use regional values of Vs (mean neutral evolutionary rate) for different time spans of primate evolution to take the different rate problem, as much as possible, into account.…”
Section: Evolutionary Trees Of the Cea-like Gene Families In Primatesmentioning
confidence: 99%
“…Neither target has therefore altered its Alu content over approximately 34 million years of primate evolution (7 million years since the divergence of human, chimpanzee and gorilla, and 10 million years since the divergence of orang-utan from this lineage). 11 Assuming a generation time of 10 years, this implies that selectivelyneutral Alu-mediated re-arrangements in this region arise at a rate of 50.9610 76 per generation (upper 95% C.I.). 12 To investigate instability in human populations, both targets were PCR amplified from 20 unrelated Caucasians for MS32 and 39 unrelated Caucasians for C1NH.…”
Section: Analysis Of Alu-mediated Deletionsmentioning
confidence: 99%